Fenômenos elétricos e estrutura da matéria : tecendo relações entre os estudos de Michael Faraday e as concepções dos estudantes - Oliveira, Everton Santos (2018)
The curricular reforms have occured in the last decades have been promoting changes in the objectives and approaches of Science Teaching; in this context, there is the defense of the insertion of the History of Science through the Contextual Approach proposed by Professor Michael R. Matthews, that is, the presentation of the socio-historical context that permeates the scientific knowledge together with the approach of concepts. The objective is to investigate how the theoretical constructs of Michael Faraday can contribute in the scope of Science Teaching, through the Contextual Approach, for scientifically more structured understandings regarding the Electrical Nature of Matter, having as reference the survey of students' conceptions expressed in the literature. The hypothesis raised is that the relation between electrical phenomena and the structure of matter can already be thought in the light of the constructs of Michael Faraday, showing the need to understand how the "particles" behaved in the electrolysis performed by this scientist. Date collection was performed by bibliographical research, which consisted in the elaboration and outline of procedures that guided the search and details of sources; for the treatment of the data was used the Content Analysis, which consists in the exhibition and interpretation of the content of all class of documents and texts from systematic descriptions and inferences. The categories established a priori were constructed in agreement with the students' conceptions obtained through the literature and with the proposal of the Contextual Approach, like: Mechanisms that theorize the constitution of the matter; Composition of matter and its relation with electricity and; External influences on the production of scientific knowledge. In terms of students' conceptions expressed in the literature, in general aspects the results show that students propose atomic models without considering their application context, do not recognize the loss / transfer of electrons as a possible model, have difficulties explaining the nature and mobility of the ions, as well as to relate the mobility of ions to the formation of the electric current. The results allow to infer that the conceptions presented by students in the high school and university present approximations with the ideas put forward during the sociohistorical period of Michael Faraday. The elements derived from this study, which are based on the Teaching-Historiography-Contextual Approach triad, are insertable in the classroom approach and can enhance the conceptual understanding, as well as the dynamics of the scientific enterprise.